Calorimetric Study with Uncertainty Analysis to Investigate the Precipitation Kinetics in a Nanostructured Al Composite. Issue 4 (30th January 2018) - Cohn, Ryan; Fullenwider, Blake; Ma, Kaka; Schoenung, Julie M.
Abstract : Nanostructured Al–Zn–Mg–Cu alloy and boron carbide/Al–Zn–Mg–Cu composite powders are fabricated through cryomilling. η'‐MgZn2 precipitation in each material is characterized through differential scanning calorimetry. The activation energy of η' precipitation is derived through Kissinger analysis. The addition of boron carbide to nanostructured Al–Zn–Mg–Cu powder increases the onset and peak temperatures of η' precipitation, but do not significantly affect the activation energy. Further analysis of uncertainties in measurement indicates that weighted least squares linear regression is a more reliable method that supplements the use of differential scanning calorimetry as a method for rapid characterization of precipitation in materials. Abstract : Precipitation kinetics in a nanostructured B4 C reinforced Al–Zn–Mg composite powder is investigated for the first time. Two linear regression methods are applied to analyze the data from differential scanning calorimetry.